KINETIC STUDY AND STATISTICAL MODELLING OF SARAWAK PEAT WATER CONTINUOUS ELECTROCOAGULATION TREATMENT PROCESS USING ALUMIMIUN ELECTRODES - ONG, CHENG EE (Universiti Malaysia Sarawak (UNIMAS), 2018)
In this globalization era, human population is growing drastically. Corresponding to the population growth, the demand for water is increasing and lead to the insufficient of water supply issues in Malaysia especially at the Sarawak isolated coastal area. For domestic usage purpose, the local residents have to rely on natural water resources such as rainwater and peat water. Consuming of peat water is harmful to human health as it contained humic substance, which affects the thyroid gland, Blackfoot disease (BFD) and others. Hence, peat water has to be treated before consumption in order to reach the allowable quality for domestic usage. The main aim of this study is to design an electrocoagulation process model using Aluminium electrode for the treatment of peat water in Sarawak. The function of the electrocoagulation system is to eliminate the turbidity and COD level in peat water by using pairs of Aluminium sacrificial electrodes which connected to a direct current power supply. The system is designed as a continuous flow reactor which operated together with equipments such as pump, filter, and magnetic stirrer. The dimension of the system is 100 cm x 15 cm x 25 cm. For this project, Microsoft Excel and Design Expert (RSM) software is used for kinetic studies, modelling and optimization function. Results of kinetic study indicated that the reaction rate constant for turbidity and COD removal at 5A current supplied is 0.0853 and 0.3841 min-1 respectively. The statistical modelling equation for both turbidity and COD removal efficiency is developed. Comparison between statistical modelling results and experimental results shows that the maximum deviation is approximately 19.27 % and 19.74% for turbidity and COD removal efficiency. The equation is verified and able to be used for scale-up function.